Genetic composition of green sea turtles (Chelonia mydas) at coastal feeding areas of Uruguay - Prosdocimi, Laura (2024)
The highly migratory and marine nature of species such as green sea turtles(Chelonia mydas) may hinder understanding of basic life history and impactensuing management and conservation applications across their full range. Toelucidate the linkages between juvenile green turtles foraging in coastal waters ofUruguay in the Southwestern Atlantic Ocean to their future nesting or feedinggrounds, this study investigated their genetic composition . A total of 201 tissuesamples were collected from turtles that had stranded or were intentionallycaptured for scientific research along the Uruguayan coast (ca. 33°–35°S) duringtwo sampling periods (2003–2005 and 2009–2014). Samples were pooled foranalysis. Twelve mitochondrial control region haplotypes and ten subhaplotypeswere identified, all of which had been previously detected at Atlantic orCaribbean nesting beaches. Mixed Stock Analysis revealed that most turtlestraced to the Ascension Island rookery, representing a substantial connectionto the remote mid-Atlantic island thousands of kilometers distant. Other nestingareas, such as Guinea Bissau in Africa and Trindade Island in Brazil, representedless significant sources. There was no significant temporal or spatial geneticstructure within Uruguayan waters, suggesting dispersion along this coast.Despite the geographic distance from the nesting beach, the significantconnection to the Ascension Island rookery underscores the importance ofconsidering rookery population size and ocean current influences inunderstanding source contributions. These findings emphasize the need forconservation efforts, including the maintenance of existing protected areas andthe creation of new ones, to ensure the long-term conservation of green turtlesconnected to various nesting colonies and feeding grounds.